1999
DOI: 10.1902/jop.1999.70.12.1429
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Periodontitis and Hyperlipidemia: Cause or Effect?

Abstract: The results of this study indicate the presence of a significant relationship between periodontitis, hyperlipidemia, and serum antibodies against P. gingivalis LPS that warrants further examination in a larger patient population. Furthermore, these studies indicate that elevated triglycerides are able to modulate IL-1beta production by PMNs stimulated with P. gingivalis LPS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
221
3
10

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 192 publications
(250 citation statements)
references
References 27 publications
16
221
3
10
Order By: Relevance
“…In addition, chewing ability may be an independent predictor of physical fitness measurements in the elderly (5 (2). This is supported by recent investigations, which found associations between impaired lipid metabolism and periodontal disease (6)(7)(8)(9)(10). Furthermore, atherosclerotic diseases such as cardiovascular diseases have recently been associated with periodontal disease (11,12).…”
Section: Periodontitis Has Been Referred To As the Sixth Complicationmentioning
confidence: 74%
See 2 more Smart Citations
“…In addition, chewing ability may be an independent predictor of physical fitness measurements in the elderly (5 (2). This is supported by recent investigations, which found associations between impaired lipid metabolism and periodontal disease (6)(7)(8)(9)(10). Furthermore, atherosclerotic diseases such as cardiovascular diseases have recently been associated with periodontal disease (11,12).…”
Section: Periodontitis Has Been Referred To As the Sixth Complicationmentioning
confidence: 74%
“…Periodontal tissue damage may thus be more expected in diabetics with hypercholesteremia, as found in our study. Some (6,9) but not all (7,10,(14)(15)(16)20) previous studies have associated hypercholesteremia with periodontal disease.…”
Section: T a B L E 1 Ch A R A C T E R I S T I C S O F S T U D Y S Umentioning
confidence: 98%
See 1 more Smart Citation
“…Recently, studies examining the relationship between periodontal disease and hyperlipidemia have shown that a greater systemic involvement may occur in patients exhibiting periodontal involvement (1)(2)(3)(4). Chronic exposure to bacterial lipopolysaccharides (LPS) can promote recruitment of defense cells which secrete alpha tumor necrosis factor (TNF-α) and interleukin-1 beta (IL-1β), thus increasing lipogenesis and lipolysis.…”
Section: Introductionmentioning
confidence: 99%
“…CP patients have elevated local levels of both Th2-and Th1-biasing cytokines (reviewed in [13,14]) and increased local numbers of DC subpopulations [15][16][17][18][19], CD4 + T cells [13][14][15][16] and B cells / plasma cells [14,20]. Many reports cite the induction of a strong humoral immune response towards P. gingivalis in adult periodontitis subjects (reviewed in [21]), including evidence for induction of high IgG antibodies to P. gingivalis LPS [22], with elevated IgG4 [23,24]. The lack of clear polarization in the cytokine response in CP [13] might be 4, and treated with indicated doses of LPS for 24 h. Culture supernatants were collected and assayed for IL-12 p70 and IP-10 by commercial ELISA (IL-10) and by CBA kit (IL-12 p70).…”
Section: Introductionmentioning
confidence: 99%